2017
DOI: 10.1111/poms.12683
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Strategic Behavior in The Competitive Newsvendor Problem: An Experimental Investigation

Abstract: This study experimentally investigates ordering behavior in the competitive newsvendor problem. We consider a duopoly market setting with two identical newsvendors selling the same perishable goods in a common market. Our experimental results show that average observed orders systematically deviate from the Nash equilibrium, and exhibit a similar pull‐to‐center pattern as in the classic non‐competitive newsvendor experiments: average orders fall below the Nash equilibrium in the high‐margin condition, and abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 53 publications
3
40
0
Order By: Relevance
“…() showed that retailer c could model q h as a random variable following a distribution with mean and standard deviation ( μ , σ ), without having to worry about h 's potential response to c 's ordering behavior. Feng and Zhang () also found evidence of stochastic ordering behavior under competition, supported by their fitting of quantal response equilibria and experience weighted attraction models. Both Ovchinnikov et al.…”
Section: Business Environmentmentioning
confidence: 81%
“…() showed that retailer c could model q h as a random variable following a distribution with mean and standard deviation ( μ , σ ), without having to worry about h 's potential response to c 's ordering behavior. Feng and Zhang () also found evidence of stochastic ordering behavior under competition, supported by their fitting of quantal response equilibria and experience weighted attraction models. Both Ovchinnikov et al.…”
Section: Business Environmentmentioning
confidence: 81%
“…There are also studies on behavioral factors that could improve decision making and mitigate risks of biased decisions in a newsvendor setting (e.g., Tomlin & Yimin, ; Bolton & Katok, ; Ockenfels & Selten, ; Ovchinnikov et al., ; Feng & Zhang, ). The ordering behavior could be affected by the background of the decisionmakers.…”
Section: Literature Classification Based On Operations Contextsmentioning
confidence: 99%
“…They showed that their model is capable of predicting newsvendor behavior and found that people are more sensitive to left-over inventory rather than lost sales. The latter finding has gathered further support from the experiments of Ovchinnikov et al (2015) and Feng and Zhang (2017).…”
Section: Literature Reviewmentioning
confidence: 60%